Kemampuan Guru Dalam Menggunakan Media Audio visual Pada Pembelajaran IPA di Kelas V SD Negeri Lamklat - Cut Khairatun Nisa; Alfiati Syafrina; Sulaiman Sulaiman (Jurnal Ilmiah Mahasiswa Pendidikan Guru Sekolah Dasar, 2023)
The purpose of this study was to describe the teacher's ability to use audio-visual media in science lessons in class V SD Negeri Lamklat Aceh Besar. The approach taken is qualitative with a descriptive research type. The subject in this study was 1 teacher of class V. Data was collected by observation and interviews. All data collected is processed with the stages of data analysis techniques, namely data reduction, data presentation, and drawing conclusions. Based on the results of the study, shows that the teacher has been able to master the three steps of using audio-visual media, namely, in the preparation step the teacher prepares a lesson plan about the material and prepares the media equipment used appropriately, in the implementation/presentation step the teacher has followed the existing indicators. such as explaining the learning objectives well, and managing the class so that students are safe and peaceful in learning. And the last follow-up step, the teacher provides exercises to see the extent to which students can understand science material correctly so that the learning process becomes more effective. So it can be concluded that the teacher has taken the steps of audio-visual media correctly so that it can be said that the teacher has the ability to use audio-visual media in science learning in class V.